2013
DOI: 10.1002/mds.25311
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of cognitive disorders in Parkinson's disease: A data‐driven approach

Abstract: The objective of this study was to identify different cognitive phenotypes in Parkinson's disease (PD) using a data-driven approach. A model-based cluster analysis was conducted on the neuropsychological test results of 558 PD patients from 2 European movement disorder centers (Lille, n = 403; Maastricht, n = 155). The number of clusters was determined according to their clinical relevance as well as on the basis of 3 statistical criteria: the cubic cluster criterion, the pseudo F statistic, and the total squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 45 publications
4
49
1
Order By: Relevance
“…Research has suggested that executive-based deficits occur earlier in the disease course due to fronto-striatal dysfunction characteristic of PD, and memory deficits do not emerge until later in the disease course. [27] However, accumulating evidence suggests a subgroup of PD patients experience more posterior cortical dysfunction, which increases risk of dementia. In one longitudinal study examining predictors of dementia in PD, patients with deficits in measures of posterior cortical function were more predictive of dementia than measures of fronto-striatal function.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that executive-based deficits occur earlier in the disease course due to fronto-striatal dysfunction characteristic of PD, and memory deficits do not emerge until later in the disease course. [27] However, accumulating evidence suggests a subgroup of PD patients experience more posterior cortical dysfunction, which increases risk of dementia. In one longitudinal study examining predictors of dementia in PD, patients with deficits in measures of posterior cortical function were more predictive of dementia than measures of fronto-striatal function.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various cognitive deficits that patients with Parkinson’s disease (PD) experience (e.g., working memory, planning, and visuospatial attention), response inhibition is of particular importance for the recognition of its negative impact on quality of life. 14 Loss of response inhibition is associated with motor symptom severity 5 and freezing of gait, a particularly debilitating feature of the disease. 69 With a close link to broader clinical deficits and prediction of later dementia, 10 response inhibition performance has been posited as a sensitive outcome measure for diagnosis and progression of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, early detection of cognitive impairment and identification of individuals at risk of dementia are major challenges. At present such classifications are usually based on clinical features that have limited prognostic value because of the heterogeneity of patients' cognitive profiles (Dujardin et al, 2013). In this issue of Brain, Nombela and colleagues perform a detailed characterization of cognitive impairment in Parkinson's disease (Nombela et al, 2014).…”
Section: Genetic Characterization Of Cognitive Impairment In Parkinsomentioning
confidence: 99%